GENETIC IMPROVMENT OF MERINO SHEEP BY USING ARTIFICIAL INSEMINATION (AI) MERINO STUD AND FEED PROCESSING AT JUNREJO – MALANG - Anom Adnyana (Journal of Innovation and Applied Technology, 2016)
The objective of this study was to disseminate the technology of Artificial Insemiation (AI) and Food Processing. This activity expected to help the Merino sheeppartner group  forovercoming their problems which subsequently it can improve their income. The methods used inthis study was to give insight knowledge and simple technology to the selected Merino sheep partner group. Basedon the discussion with Merino sheep partner group, several activities were carried out, i.e.: (1) facilitating somegood quality of Merino sheep lifestoocks, (2) providing technology of alternative food production with cooper, (3) training of productionand financial management, (4) demo-reproduction management and (5) monitoring and evaluation. The result of this studyshowed that theMerino sheep partner group could master the technique of the technique of selecting superior sires ,parent management, fertilizer production engineering, manufacture and management of alternative feed production and reproduction as well as the financial well.